What the eyes say about planning of focused referents during sentence formulation: a cross-linguistic investigation - Ganushchak, Lesya Y.; Konopka, Agnieszka E.; Chen, Yiya (Frontiers in Psychology, 2014)
This study investigated how sentence formulation is influenced by a preceding discourse context. In two eye-tracking experiments, participants described pictures of two-character transitive events in Dutch (Experiment 1) and Chinese (Experiment 2). Focus was manipulated by presenting questions before each picture. In the Neutral condition, participants first heard ‘What is happening here?’ In the Object or Subject Focus conditions, the questions asked about the Object or Subject character (What is the policeman stopping? Who is stopping the truck?). The target response was the same in all conditions (The policeman is stopping the truck). In both experiments, sentence formulation in the Neutral condition showed the expected pattern of speakers fixating the subject character (policeman) before the object character (truck). In contrast, in the focus conditions speakers rapidly directed their gaze preferentially only to the character they needed to encode to answer the question (the new, or focused, character). The timing of gaze shifts to the new character varied by language group (Dutch vs. Chinese): shifts to the new character occurred earlier when information in the question can be repeated in the response with the same syntactic structure (in Chinese but not in Dutch). The results show that discourse affects the timecourse of linguistic formulation in simple sentences and that these effects can be modulated by language-specific linguistic structures such as parallels in the syntax of questions and declarative sentences.